Strategi Pengembangan Kapasitas Pemerintah Daerah Untuk Mewujudkan Good Governance Di Kantor Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Sidenreng Rappang - T. Taufik; Muh.Rohady Ramadhan; Abdul Jabbar (Public Inspiration : Jurnal Administrasi Publik, 2025)
The performance of civil servants (ASN) is essential in realizing good governance at the local government level. However, challenges such as weak discipline, low competence, and limited capacity development still persist. This study aims to examine the capacity development strategy of the Regional Civil Service and Human Resource Development Agency (BKPSDM) of Sidenreng Rappang Regency in implementing good governance. Using a descriptive quantitative approach, data were collected through questionnaires, interviews, and observations from 35 respondents (total sampling). Data were analyzed using descriptive statistics with SPSS version 21. The results show that the implementation of capacity development, including training and discipline programs, is categorized as good with an average score of 70.5%. Competency management—measured through Spencer’s five dimensions: knowledge, skills, self-concept, traits, and motives—achieved a score of 70.4%. The realization of good governance, based on indicators such as transparency, participation, responsiveness, responsibility, and rule of law, scored 71.6%. These findings confirm that capacity building and structured competency management positively influence the quality of local governance. This research advances the current understanding in public administration by linking internal bureaucratic development with the effectiveness of governance practices in local institutions.